2014
DOI: 10.1016/j.colcom.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Infrared to Visible Up-conversion in Biocellulose–yttrium Vanadate Nanoparticle Composite Membranes. Demonstration of Chloroaluminum Phthalocyanine Light Emission Under Up-converted Light Excitation

Abstract: Biocellulose Chloroaluminum phthalocyanine Yttrium vanadate nanoparticles lanthanide ions photodynamic therapy photosensitizers drug delivery systems biomaterials composite membranes YVO 4 :(Yb 3+ -Er 3+ /Ho 3+ ) nanoparticles were incorporated in biocellulose membranes obtained from Gluconacetobacter xylinus. Materials present the property of converting near-infrared (NIR) into higher-energy visible light. Nanoparticles were prepared by optimizing towards higher emission intensity at the absorption wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…After sintering, the product was crushed and then wetly ballmilled again for 24 h. The sintering steps and parameters were at 950 °C for 2 h and then at 1100 °C for 48 h, with a heating ramp of 5 °C min -1 and a cooling ramp of 10 °C min -1 down to room temperature. YVO 4 :Yb 3+ :Er 3+ nanoparticles YVO 4 :Yb 3+ :Er 3+ upconversion nanoparticles (UCNPs) were synthesized according to the method previously reported by Nigoghossian et al 40 The method consists in a co-precipitation of sodium citrate 2 M (5 mL) and lanthanide ions. The latter is a mixture of aqueous solutions (1 M) of yttrium nitrate and ytterbium and erbium chlorides in a defined molar ratio (Y:Yb:Er = 77.5:20:2.5).…”
Section: Apatitementioning
confidence: 99%
“…After sintering, the product was crushed and then wetly ballmilled again for 24 h. The sintering steps and parameters were at 950 °C for 2 h and then at 1100 °C for 48 h, with a heating ramp of 5 °C min -1 and a cooling ramp of 10 °C min -1 down to room temperature. YVO 4 :Yb 3+ :Er 3+ nanoparticles YVO 4 :Yb 3+ :Er 3+ upconversion nanoparticles (UCNPs) were synthesized according to the method previously reported by Nigoghossian et al 40 The method consists in a co-precipitation of sodium citrate 2 M (5 mL) and lanthanide ions. The latter is a mixture of aqueous solutions (1 M) of yttrium nitrate and ytterbium and erbium chlorides in a defined molar ratio (Y:Yb:Er = 77.5:20:2.5).…”
Section: Apatitementioning
confidence: 99%
“…The ability of these compounds to suppress the superoxide production by macrophages seems to modulate the secretion of protein kinases in tumor cell proliferation and induce the expression of anticarcinogenic enzymes [34,35]. Recent studies have demonstrated that PDT is not restricted to visible light; deep tissue penetration in PDT could also be achieved with near-infrared (NIR) laser radiation, followed by upconversion to higher-energy visible or ultraviolet light in the biological medium [36,37].…”
Section: Interaction Of Light In the Skinmentioning
confidence: 99%
“…Optical materials containing lanthanide (Ln) ions are widely studied due to their promising potential for application in many fields of science and industry. [1][2][3][4][5][6][7][8][9][10][11] This is because these materials are capable of generating luminescence, 9,12 i.e. emission of light resulting from the excitation of electrons of a given material with radiation from the ultraviolet (UV), visible or near-infrared (NIR) spectral ranges and their subsequent radiative relaxation to the ground states.…”
Section: Introductionmentioning
confidence: 99%